An Engineered Probiotic Produces a Type III Interferon IFNL1 and Reduces Inflammations in in vitro Inflammatory Bowel Disease Models - Chua, Koon Jiew (AMER CHEMICAL SOC, 2023)
10.1021/acsbiomaterials.2c00202